(untitled) (International Journal of Natural Sciences, 2012)
Sylhet City Corporation (SCC) of Bangladesh is supplying water to the Sylhet city dwellers through its distribution network. The quality of water is at risk to deteriorate during its flow through the distribution system and also due to probability of high elemental concentrations in groundwater. To identify such probable water contamination problems; water samples from 20 (out of 27) different wards of the city were analyzed in this study. The parameters analyzed were pH, turbidity, total alkalinity as Calcium carbonate CaCO3, total hardness, iron, manganese, arsenic, chloride, fluoride, MPN (Most Probable Number), total viable count (TVC), coliform and fecal coliform. The study revealed that all the physico-chemical parameters except alkalinity were in the permissible limit. All the samples were found to have total alkalinity as CaCO3 value higher than the WHO and Bangladesh Standards limit. But the water from treatment plant was found to have high turbidity and iron concentration. Analysis of microbial water quality parameters revealed that there was no coliform and fecal coliform contamination. But high value of MPN index and total viable count indicates that there were obvious contamination and chances of contamination by non-fecal pathogens. Finally, it is concluded and recommended that the water treatment facilities of SCC have to be improved, further investigation should be done to identify the non-fecal organisms and the cause of high total viable bacteria should be detected and corrected for the betterment of the city dwellers. DOI: http://dx.doi.org/10.3329/ijns.v2i1.10881 International Journal of Natural Sciences (2012), 2(1): 33-37